2016
DOI: 10.1038/nn.4327
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional prefrontal-hippocampal interactions support context-guided memory

Abstract: We compared the dynamics of hippocampal and prefrontal interactions in rats as they used spatial contexts to guide the retrieval of object memories. Upon context entry, functional connectivity analysis indicated a flow of contextual information from the hippocampus to prefrontal cortex. Conversely, upon the onset of object sampling, the direction of information flow reversed, consistent with prefrontal control over the retrieval of context-appropriate hippocampal memory representations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
137
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(162 citation statements)
references
References 25 publications
23
137
0
Order By: Relevance
“…In particular, left anterior HPC showed greater functional connectivity during the early phase of learning with regions of mPFC, a finding predicted by SUSTAIN's neural framework (11). These results are also consistent with episodic memory findings that PFC biases encoding and retrieval of mnemonic information in HPC (9,27,28) and a recent proposal (29) that memories for individual experiences are updated through HPC-mPFC interactions to create generalized knowledge that supports complex behaviors like inference (8,30). We also found that early-learning HPC activation was coupled with regions implicated in a neural hierarchy of cognitive control along the rostral-caudal axis of lateral PFC (26,57,58).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In particular, left anterior HPC showed greater functional connectivity during the early phase of learning with regions of mPFC, a finding predicted by SUSTAIN's neural framework (11). These results are also consistent with episodic memory findings that PFC biases encoding and retrieval of mnemonic information in HPC (9,27,28) and a recent proposal (29) that memories for individual experiences are updated through HPC-mPFC interactions to create generalized knowledge that supports complex behaviors like inference (8,30). We also found that early-learning HPC activation was coupled with regions implicated in a neural hierarchy of cognitive control along the rostral-caudal axis of lateral PFC (26,57,58).…”
Section: Discussionsupporting
confidence: 79%
“…Prefrontal cortex (PFC) is proposed to tune selective attention to features (24)(25)(26), as well as direct encoding and retrieval of HPC cluster representations (9,(27)(28)(29)(30). In particular, PFC monitors the similarity between the current stimulus information and existing conceptual knowledge and biases HPC functions in reorganizing clusters to reflect goal-relevant features.…”
mentioning
confidence: 99%
“…Reinstatement of behaviorally relevant memories within hippocampus during spatial learning may be particularly dependent on top-down influence from mPFC [10]. When rodents make decisions that depend on spatial context, mPFC drives hippocampal responses [9], suggesting that mPFC coordinates reinstatement of hippocampal memory representations that are most relevant to ongoing experience [27]. Increased hippocampal—mPFC coupling is also observed during spatial memory retrieval in humans [28, 29], and such coupling has been further shown to support individuals’ ability to connect past and present experience [17, 18, 30].…”
Section: Integration Of Spatial Experiencementioning
confidence: 99%
“…Memory integration is thought to be supported by bidirectional interactions between hippocampus and medial prefrontal cortex (mPFC) [9, 10]. Reactivation of related memories during new events is mediated by hippocampal pattern completion processes that allow for reinstatement of entire memory traces from overlapping input [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation